Evaluation of capacity building programme of district health managers in India: a contextualised theoretical framework - N S ePrashanth; Bruno eMarchal; Guy eKegels; Bart eCriel (Frontiers Media S.A., 2014)
Performance of local health services managers at district level is crucial to ensure that health services are of good quality and cater to the health needs of the population in the area. In many Low- and Middle-Income Countries (LMIC), health services managers are poorly equipped with public health management capacities needed for planning and managing their local health system. In the South Indian Tumkur district, a consortium of five non-governmental organisations partnered with the state government to organise a capacity-building program for health managers. The program consisted of a mix of periodic contact classes, mentoring and assignments and was spread over 30 months. In this paper, we develop a theoretical framework in the form of a refined program theory to understand how such a capacity-building program could bring about organisational change. A well-formulated program theory enables an understanding of how interventions could bring about improvements and an evaluation of the intervention. In the refined program theory of the intervention, we identified various factors at ¬individual, institutional and environmental levels that could interact with the hypothesised mechanisms of organisational change, such as staff's perceived self-efficacy and commitment to their organisations. Based on this program theory, we formulated context-mechanism-outcome configurations that can be used to evaluate the intervention and, more specifically, to understand what worked, for whom and under what conditions. We discuss the application of program theory development in conducting a realist evaluation. Realist evaluation embraces principles of systems thinking by providing a method for understanding how elements of the system interact with one another in producing a given outcome.